Palaeoclimatic impacts on the phylogeography of an Afro-montane liverwort: Jamesoniella colorata (Lophoziaceae ) - Chase, Rachel Renee (Department of Biological Sciences, 2019)
The mechanisms behind the high level of plant diversity and endemism observed in the Cape Floral Region (CFR) of South Africa have been the focus of many studies. Recently developed methods that employ DNA sequence data are making major contributions in reconstructing evolutionary histories of CFR species. Concurrently, palaeoenvironmental evidence is used increasingly to explain the impact of past climates on species ranges. This paper combines these two approaches by analysing the distribution of genetic diversity of the Afro-montane liverwort Jamesoniella colorata and associating its inferred evolutionary history with major palaeoclimatic trends in South Africa. Liverworts are generally well-suited for phylogeographical studies because they often have low dispersal rates, broad geographical ranges and long evolutionary persistence. In addition, the high among-population diversity observed in J colorata is conducive to the interpretation of significant historical events. The GIS-based bioclimatic envelope shows a strong correlation between potential habitat and the known distribution of J colorata and indicates that sampling in this study was sufficient to make accurate phylogeographical inferences. A combination of phylogeographical data and population genetics evidence suggests that populations of J colorata in the Western Cape Province have experienced range contractions into upper-montane refugia and range expansions into lower altitudes in response to warming and cooling climatic trends, respectively. These range shifts have probably taken place throughout the Quaternary glacial-interglacials cycles, , which are thought to have been influential in shaping modem patterns of diversity. In lV an attempt to assign approximate dates to the two expansion events inferred for J. colorata, an average chloroplast mutation rate was applied to the trnL-F cpDNA mismatch distribution. The results roughly place the expansions within the last glacial period, demonstrating the general accordance of the phylogeographical and palaeoclimatic data. The molecular work in this study also brought into question the taxonomic status of several specimens that showed distinctly divergent DNA sequences. Preliminary morphological inspection of the specimens revealed subtle but clear differences in leaf and stem anatomy that were once associated with J. oenops, a species synonymised with J. colorata in 1971.